Marvel - absolutely everything you need to know ... ab - Bray, Adam; Cink, Lorraine; Sazaklis, John; Wilson, Sven (Dorling Kindersley Limited, 2016)
Packed with fun facts, bizarre-but-true tales, and quirky insights into everyone's favorite Marvel comic characters, including The Avengers, Spider-Man, and Daredevil. little-known facts and information about the iconic Marvel characters